Biosynthesis of low molecular weight antifungal protein from aspergillus giganteus in batch fermentation and in-vitro assay - Dutta D.; Debnath M. (My University, 2025)
In present study, Taguchi's design of experiment L9 orthogonal array was created using Qualitek-4 software with four most critical factors namely, K2HPO4, MgSO4, CaCl2 and culture pH. Production of a new intracellular antifungal protein in submerged fermentation was optimized with yield of 0.98±0.1 mg/gram dry cell weight mycelia from Aspergillus giganteus MTCC 8408. The average molecular mass of the purified protein was figured as 5.122 kDa using Electro Spray Ionization-Mass Spectrometry. Scanning electron microscopy was used to correlate the effect of selected factors on fungal cell morphology and its metabolite production. In vitro antifungal susceptibility assay was profiled against Aspergillus Niger and minimum inhibitory concentrations were in the range 0.3±0.06 μg/ml. The stronger influencing factors on afp production and mycelial biomass were noted with CaCl2 and K2HPO4 respectively. The validation experiments using optimized conditions confirmed an improvement in afp by 3.86 times with mycelial biomass by 1.52 times, compared to the basal medium. The present statistical optimization study revealed an opportunity to promote economical design at the industrial level for future scale up of effective antifungal agent against systemic aspergillosis as well as possible post harvest loss. © 2018 Taylor and Francis Ltd. All rights reserved.